Application of Transformational Leadership Principles in School Management (Case Study at SMP Negeri 1 Bojongsoang) - Endang Komara; Agus Mulyanto; Ai Sumarni; Marpuah Marpuah; Siti Saadah (Edumaspul: Jurnal Pendidikan, 2023)
The application of the principles of transformational leadership in school management is very important to improve the quality of education, so this is the background of this research. This study aims to explain the Principles of Transformational Leadership in School Management (Case Study at SMP Negeri 1 Bojongsoang). This study uses a qualitative research method with a case study approach and is descriptive in nature. The place and time of this research is SMP Negeri 1 Bojongsoang in the Even Semester 2022/2023. Data collection techniques namely observation, interviews and documentation. The informants/sources of information in this study were the principal, deputy principal and teachers of SMP Negeri 1 Bojongsoang. Data analysis techniques carried out were data reduction, data presentation, and verification. The results of this study explain 1) Transformational leaders are leaders who have far-reaching insights and seek to improve and develop the organization not only for now but in the future as well, 2) Transformational leadership is based on four main dimensions, namely Idealized Influence, Inspirational Motivation, Intellectual Stimulation , and Individualized Consideration, 3) The principles of transformational leadership include Simplification, Motivation, Facilitation, Innovation, Mobility, Alertness, and Determination, and 4) Application of the Principles of Transformational Leadership in School Management at SMP Negeri 1 Bojongsoang includes a clear inspirational vision, individual development, intellectual stimulation, ideal influence, inspiration and motivation, and empowerment and delegation.